Study of Risk Factors in Global Stock Markets During the COVID-19 Pandemic Under Different Market Conditions - Francisco Jareño; María-Isabel Martínez-Serna; Pablo Sánchez (SAGE Open)
In this paper, we examine the stock markets’ response to fluctuations in international risk factors under different market states during the COVID-19 pandemic. Using data from seven countries heavily affected by the sanitary crisis, over the period between January 2020 and December 2021, we estimate an extended risk factor model through the quantile regression approach, with the purpose of identifying distinct sensitivities to risk sources depending on the bullish or bearish state of the market. Our results suggest higher explanatory ability at extreme quantiles, thereby revealing significant disparities in sensitivities, that are found to be dependent on the market conditions, on the country and on the particular risk factor. JEL classification : C22, C51, F21, G12, G32, H12